C3 ‐dependent effector functions of complement - Zarantonello, Alessandra; Revel, Margot; Grunenwald, Anne; Roumenina, Lubka T. (Immunological reviews, 2023)
C3 is the central effector molecule of the complement system, mediating its multiple functions through different binding sites and their corresponding receptors. We will introduce the C3 forms (native C3, C3 [H 2 O], and intracellular C3), the C3 fragments C3a, C3b, iC3b, and C3dg/C3d, and the C3 expression sites. To highlight the important role that C3 plays in human biological processes, we will give an overview of the diseases linked to C3 deficiency and to uncontrolled C3 activation. Next, we will present a structural description of C3 activation and of the C3 fragments generated by complement regulation. We will proceed by describing the C3a interaction with the anaphylatoxin receptor, followed by the interactions of opsonins (C3b, iC3b, and C3dg/C3d) with complement receptors, divided into two groups: receptors bearing complement regulatory functions and the effector receptors without complement regulatory activity. We outline the molecular architecture of the receptors, their binding sites on the C3 activation fragments, the cells expressing them, the diversity of their functions, and recent advances. With this review, we aim to give an up‐to‐date analysis of the processes triggered by C3 activation fragments on different cell types in health and disease contexts.